The influence of pre-heat treatment on white cast irons plasticity - Myronova, T. M. (Science and Transport Progress, 2013)
Purpose. The development of heat treatment modes of white cast irons for structure changes in their eutectic constituent, namely in disturbing the monolithic structure of ledeburite colonies cementite structure and eutectic net continuity. Also the mentioned heat treatment modes are targeted to the eutectic net shift for the most suitable position from the point of plastic deforming. Methodology. The hypoeutectic white cast irons with 2.92…3.35 % carbon content and additionally alloyed by 3.18 % vanadium have been used as the research materials. The mentioned alloys have been pre-heat treated and hot twist tested. Findings. The research results showed that the carbide net breaking by plastic deforming leads to cast irons mechanical properties increasing but has difficulties in implementation due to the white cast irons low plasticity. The influence of different pre-heat treatment modes on structure and plasticity of white hypoeutectic cast irons have been investigated. They include the isotherm soaking under the different temperatures as well as multiply soakings and thermo-cycling. The influence of eutectic level, as well as pre heat treatment modes on different composition white cast irons hot plasticity have been investigated. Originality. It was determined that the heat treatment, which leads to double α→γ recrystallization under 860 – 950 °С and reperlitization under 720-680 °С results in significant increase of plasticity, as well as in un-alloyed and alloyed by vanadium white cast irons. It takes place due to carbide matrix phase separation in ledeburite colonies by new phase boundaries forming especially due to carbide transformations under vanadium alloying. Practical value. The implementation of pre-heat treatment with phase recrystallization resulted in hypoeutectic white cast irons plasticity increasing. The obtained level of cast iron plasticity corresponds to the one of carbide class steels, which ensures the successful deformation by forging and rolling.